Karantina Tumbuhan di Indonesia dalam Masa Perdagangan Bebas: Plant quarantine in indonesia in free trade era - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Plant quarantine is enacted to keep out foreign plant pests and to protect food, horticulture and estate crops from alien pests. The act prohibits or restricts entry into or passage through a country from foreign countries of plants, plant products, soil, and other materials carrying or likely to carry pests not known to be established in the country. Experienced inspectors stationed at all points of entry into the country enforce quarantine of produce likely to introduce new pests. The importance of plant quarantine becomes more and more significant in the free trade era. Indonesia to be one of potential market for many agricultural products has still very limited number of plant quarantine inspectors. Number and quality of plant quarantine inspectors are badly needed in ,order enable coping the problems. Education and training should be organized and it is important to include plant quarantine in the Faculty of Agriculture curriculum. Key words: plant quarantine, free trade, plant quarantine inspectors INTISARI Pemberlakuan Karantina Tumbuhan dimaksudkan untuk mencegah masuknya hama dan patogen asing dan melindungi tanaman-tanaman pangan, hortikultura dan perkebunan dari hama dan patogen asing itu. Tindakan karantina berupa pelarangan atau pembatasan masuknya atau lewatnya tamanam, produk tanaman dan bahan-bahan lain yang membawa atau dapat membawa hama dan patogen yang belum ditemukan di dalam negara atau wilayah tertentu. Karantina tumbuhan dilaksanakan oleh petugas-petugas karantina yang ditempatkan di semua tempat masuk. Arti karantina tumbuhan menjadi semakin penting dalam era perdagangan bebas. Indonesia yang merupalcan salah satu pasar potensial untuk banyak produk tanaman memiliki jumlah petugas karantina tumbuhan yang masih sangat sedikit. Jumlah dan kualitas petugas-petugas karantina yang mencukupi sangat diperlukan untuk dapat mengatasi masalah-masalah karantina. Pendidikan dan pelatihan sangat diperlukan clan sangat penting untuk memasukkan ICarantinaTumbuhan di dalam kurikulum Fakultas Pertanian. Kata-kata kunci: karantina tumbuhan, perdagangan bebas, petugas karantina tumbuhan